Individual heart rate assessment and bout analysis of vigorous physical activity in children. Issue 3 (27th April 2022) - Van Camp, Carole M.; Batchelder, Sydney R.; Irwin Helvey, Casey
Abstract : Children should engage in 1 hr/day of moderate‐to‐vigorous physical activity (MVPA) that results in increased heart rates (HRs) (CDC,  2022). However, precise individualized HR criteria for MVPA are not provided, and it is unclear whether observed behaviors classified as MVPA are associated with elevated HRs indicative of MVPA. The current study replicated an individualized heart rate assessment (IHRA) for identifying MVPA HR zones in children (Van Camp et al.,  2021). We then evaluated whether engaging in vigorous PA (VPA) for half of the session resulted in HRs indicative of VPA for at least half of the session when children engaged in running for 30, 60, 90, and 120 s bouts. Individual differences were observed during the IHRA. During the bout analysis, HRs were not within VPA zones for 50% of the session. However, HRs were within moderate PA (MPA) zones, with 30 s bouts producing the highest percentages of MPA.